2019
DOI: 10.1136/postgradmedj-2018-136269
|View full text |Cite
|
Sign up to set email alerts
|

Waiting it out: consultation delays prolong in-patient length of stay

Abstract: BackgroundDecreasing delays for hospitalised patients results in improved hospital efficiency, increased quality of care and decreased healthcare expenditures. Delays in subspecialty consultations and procedures can cause increased length of stay due to reasons outside of necessary medical care.ObjectiveTo quantify, describe and record reasons for delays in consultations and procedures for patients on the general medicine wards.MethodologyWe conducted weekly audits of all admitted patients on five Internal Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 28 publications
(10 reference statements)
0
18
0
Order By: Relevance
“…Residents may withdraw the request for a consultation with fellows due to the difficulty. Therefore, because delays in consultation can have a negative impact on patient care [ 9 ], consultants should be aware that they need to demonstrate a willingness to accept consultation requests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Residents may withdraw the request for a consultation with fellows due to the difficulty. Therefore, because delays in consultation can have a negative impact on patient care [ 9 ], consultants should be aware that they need to demonstrate a willingness to accept consultation requests.…”
Section: Discussionmentioning
confidence: 99%
“…It includes providing professional recommendations, writing notes, following up on patients daily, and teaching residents [ 1 , 2 ]. In recent years, the number of consultations has increased [ 4 ], and there have been numerous reports of the positive association between consultations and favourable patient outcomes, including associations with reduced mortality [ 5 7 ], readmission [ 6 , 8 ], and length of stay [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…6,7 In high complexity environments, long waiting lists and delays in service delivery unnecessarily increase length of hospitalization time. 8 Difficulty in getting appointments is one of the main causes of dissatisfaction, given that having to wait for long periods of time generally results in shorter consultations. 8 Whereas waiting time is attributed to organizational processes, length of consultation is characterized by health demands and concerns, that differ between individuals and, for this reason, require empathetic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…8 Difficulty in getting appointments is one of the main causes of dissatisfaction, given that having to wait for long periods of time generally results in shorter consultations. 8 Whereas waiting time is attributed to organizational processes, length of consultation is characterized by health demands and concerns, that differ between individuals and, for this reason, require empathetic interactions. 9 Greater length of medical consultation time does not necessarily improve Primary Health Care performance results, including prescriptions issued, requests for laboratory tests and referrals, or patient satisfaction with the service provided.…”
Section: Introductionmentioning
confidence: 99%
“…We would like to commend Rahman et al for their work highlighting the reasons for delays in inpatient consultations 1. The authors found that miscommunication between referring and receiving teams was responsible for 34% of all delays each with an average delay of 1.6 days in length of stay (combining communication and power dynamic categories).…”
mentioning
confidence: 99%